Analisis dan Perancangan Website pada Girya Gerabah Usaha Kecil Menengah (UKM) Abad 16 Estetika - Ruth Mariana Bunga Wadu; Rio Wirawan (Jurnal Informatika Universitas Pamulang, 2021)
Information is obtained very quickly with the internet media, so all information can be obtained from the palm of the hand. With fast information, it is certain that the promotion given to an SME can spread quickly. In this study, yes, because of that, vigorous promotion will be able to help SMEs in developing their products. SMEs as one of the business actors must be able to take advantage of the development of digital technology as a form of effort to maintain business continuity, so that the Indonesian people have begun to be aware of online transactions with this, online transaction sales have started to increase and the market is very wide open so that the increase in sales can be very large. increase. The problem that occurs is that some SME business actors still do not know that with a good brand and quality product quality, it will be able to increase sales, especially in the pottery field which was raised in this research problem. With the best quality pottery in Indonesia, sales will increase significantly. because it has a worldwide market. This also happened to the Aesthetic 16th Century UKM. research, analysis and website design using internet facilities as a medium of communication and information exchange so that the pottery sales process becomes faster.